PERFURAÇÃO DE POÇOS TUBULARES NA REGIÃO OESTE DO ESTADO DO PARÁ - Oliveira, Josafá Ribeiro de; Schalken, Charles George P. S.; Pastama, José Maria do Nascimento; Leal, José Waterloo (Águas Subterrâneas, 2001)
Resumo não disponível.